2007
DOI: 10.1111/j.1440-1797.2007.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n‐3 fatty acids on nutritional status and inflammatory markers in haemodialysis patients

Abstract: A dietary regime with fish oil could be used in dialysis patients to slow down the development of atherosclerosis and improve nutritional parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 34 publications
2
56
0
2
Order By: Relevance
“…The essential fatty acid deficiency that caused by the accelerated lipid peroxidation at the low Hb level might be explained by oxidative stress due to the anemic condition itself. A double-blind study of patients on hemodialysis who received either fish oil, olive oil, or safflower oil had documented that patients may have increased levels of the proinflammatory prostaglandin PGE2 and that fish oil intervention may decrease these levels and improves hematocrit levels [11,37,38]. The present study showed that the relative abundance of the saturated fatty acid and the relative deficiency of eicosapentaenoic acid were greater in the plasma of HD-CAD pediatric patients than that in HD-norm.…”
Section: Discussionmentioning
confidence: 47%
“…The essential fatty acid deficiency that caused by the accelerated lipid peroxidation at the low Hb level might be explained by oxidative stress due to the anemic condition itself. A double-blind study of patients on hemodialysis who received either fish oil, olive oil, or safflower oil had documented that patients may have increased levels of the proinflammatory prostaglandin PGE2 and that fish oil intervention may decrease these levels and improves hematocrit levels [11,37,38]. The present study showed that the relative abundance of the saturated fatty acid and the relative deficiency of eicosapentaenoic acid were greater in the plasma of HD-CAD pediatric patients than that in HD-norm.…”
Section: Discussionmentioning
confidence: 47%
“…Another hypothesis for the cardioprotective effects of fish oil supplementation is the inhibition of cytokine production, as measured directly in plasma or ex vivo, and studies have been published that support and challenge the hypothesis that n-3 LCP inhibit cytokine and CRP production (102,103,(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) . In their recent meta-analysis including twenty-one trials, Balk et al (151) concluded that the effect of n-3 LCP, including EPA and DHA, on CRP levels in human subjects was unconvincing.…”
Section: Effects Of Epa and Dha On Inflammationmentioning
confidence: 99%
“…Administration of EPA would be expected to help correct the relative EPA deficiency reported in hemodialysis patients [30,31,32] and increase the EPA/AA ratio that has been inversely associated with adverse CV events and markers of inflammation in this population [35,54]. The potential benefit in reducing CV risk would be expected to be associated with low treatment risk, given the well-characterized safety profile reported in the literature [40,41]; however, this profile needs to be confirmed in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…EPA levels in a study of 42 hemodialysis patients were negatively correlated with concentrations of the proinflammatory cytokines tumor necrosis factor-α ( r = −0.497; p < 0.05) and IL-6 ( r = -0.468; p = 0.03) [54]. In populations other than hemodialysis patients, EPA has been shown to increase the levels of anti-inflammatory cytokines and reduce the levels of the proinflammatory cytokines [44,55,56].…”
Section: Eicosapentaenoic Acid As a Potential Therapeutic Approach Tomentioning
confidence: 99%